Impact of Continuous and Seasonal Breeding on Performance of Surti Goats - Belsare, V.P.; Parmar, C.P.; Chaudhari, D.V. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The profitability of goat enterprise depends on successful rearing of more number/per cent of kids on goat farm. This study was carried out to compare the performance of Surti goat under continuous and seasonal breeding pattern at Surti goat farm of the station for a period of four years. The goats were maintained on stall feeding and managed as per standard procedure. The number of kidding, kid born, their mortality and successful rearing of kids for one year of age were studied. The numbers of females under continuous and seasonal breeding were 283 and 303. The kidding percentage was 74.55 and 39.93 for continuous and seasonal breeding respectively, which indicates that the breeding performance is much higher in continuous breeding thereby getting more number of kids (227), while in seasonal breeding kidding per cent was very less and number of kids available for rearing were also less (134). However, the incidence of mortality was much higher in continuous breeding 41.85% (95) with the availability of 58.14% (132) of kids for rearing, whereas in seasonal breeding mortality was 32.08% (43) with the availability of 67.92% (91) kids for rearing. Grossly, the overall percentage availability of kids for rearing is more in continuous breeding, hence to optimize the profit of goat farm continuous breeding is better than seasonal breeding with a precautionary measures to control kid mortality.